Optimasi Formulasi Krim Minyak Jintan Hitam (Nigella Sativa Linn) Dengan Variasi Konsentrasi Asam Stearat Dan Trietanolamin - Rico Sentosa Sihombing; Rena Meutia (Jurnal Ventilator, 2023)
Black cumin oil (Nigella Sativa Linn) is rich in antioxidants. One of the substances contained in black cumin oil (Nigella Sativa Linn) which acts as an antioxidant is thermoquinone. Cream is a widely chosen preparation because it is one of the pharmaceutical preparations that is used topically for the treatment of various skin diseases. The purpose of this study was to determine whether Cumin (Nigella Sativa Linn) Oil (Nigella Sativa Linn) can be formulated as a cream dosage form. to find out the optimum concentration of black cumin oil cream formulation (Nigella Sativa Linn) with cream base variations (Stearic acid and TEA).This research is a longitudinal-experimental study. The tools used in this study were glassware, watch glass, evaporating cup, parchment paper, universal pH indicator, digital scale, mortar, stamper, waterbath, refrigerator, stirring rod, tweezers, spirit lamp, loop needle. The materials used in this study were Black Cumin (Nigella Sativa Linn) oil, TEA, White wax, Stearic Acid, White Vaseline, Methyl paraben, PEG, Aquadest. For organoleptic testing of cream, it can be seen from the observation of color, smell, and texture. The evaluation was carried out including organoleptic tests for homogeneity, absorption, and pH tests. Based on the research results, it can be concluded that black cumin oil can be formulated into cream preparations with varying concentrations of stearic acid and triethanolamine, although there are several tests that do not meet the requirements for cream preparation tests. The combination of stearic acid and triethanolamine with different concentrations can affect the physical quality which includes pH, spreadability and mechanical stability but has no effect on the organoleptic, cream type and homogeneity.